Proceedings of the 2018 Workshop on Multimedia for Accessible Human Computer Interface 2018
DOI: 10.1145/3264856.3264858
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Symbol Discrimination on a Small Pin-array Display

Abstract: Pin-array displays are a promising technology that allow to display visual information with touch, a crucial issue for blind and partially sighted users. Such displays are programmable, therefore can considerably increase, vary and tailor the amount of information as compared to common embossed paper and, beyond Braille, they allow to display graphics. Due to a shortage in establishing which ideal resolution allows to understand simple graphical concepts, we evaluated the discriminability of tactile symbols at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…These studies showed high recognition rates. Depending on the size of the matrix and the space between the pins the recognition rates varied from 60% to 90% in blind and sighted adults (Bellik & Clavel, 2017;Leo, Baccelliere, Waszkielewicz, Cocchi, & Brayda, 2018;Velazquez et al, 2008). Moreover, Zarate et al (2017) showed that several usage scenarios for people with visual impairments can be implemented with their Blindpad device (12 × 16 matrix of 4 mm pins spaced 4 mm apart).…”
Section: Pin Array Tablets and Raised Dot Pictogramsmentioning
confidence: 99%
“…These studies showed high recognition rates. Depending on the size of the matrix and the space between the pins the recognition rates varied from 60% to 90% in blind and sighted adults (Bellik & Clavel, 2017;Leo, Baccelliere, Waszkielewicz, Cocchi, & Brayda, 2018;Velazquez et al, 2008). Moreover, Zarate et al (2017) showed that several usage scenarios for people with visual impairments can be implemented with their Blindpad device (12 × 16 matrix of 4 mm pins spaced 4 mm apart).…”
Section: Pin Array Tablets and Raised Dot Pictogramsmentioning
confidence: 99%
“…One way to take the advantage is by using pin array stimulation. The spatiotemporal patterns of the pin array can be used to convey information such as directions and icons [8,9]. In this tutorial, Jingun Jung describes two studies using PinPad hardware that combines a pin array and a touchpad.…”
Section: Part 4: Pin Array Displaymentioning
confidence: 99%